Parkinson's Disease Modification Through Abl Kinase Inhibition: An Opportunity. Issue 1 (23rd November 2021) - Werner, Milton H.; Olanow, C. Warren
ABSTRACT: Parkinson's disease (PD) is the second most prevalent neurodegenerative disease of the central nervous system, with an estimated 5 000 000 cases worldwide. Historically characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta, PD pathology is now known to be widespread and to affect serotonin, cholinergic and norepinephrine neurons as well as nerve cells in the olfactory system, cerebral hemisphere, brain stem, spinal cord, and peripheral autonomic nervous system. PD pathology is characterized by the accumulation of misfolded α‐synuclein, which is thought to play a critical role in the etiopathogenesis of the disease. Animal models of PD suggest that activation of the Abelson tyrosine kinase (c‐Abl) plays an essential role in the initiation and progression of α‐synuclein pathology and neurodegeneration. These studies demonstrate that internalization of misfolded α‐synuclein activates c‐Abl, which phosphorylates α‐synuclein and promotes α‐synuclein pathology within the affected neurons. Additionally, c‐Abl inactivates parkin, disrupting mitochondrial quality control and biogenesis, promoting neurodegeneration. Post‐mortem studies of PD patients demonstrate increased levels of tyrosine phosphorylated α‐synuclein, consistent with the activation of c‐Abl in human disease. Although the c‐Abl inhibitor nilotinib failed to demonstrate clinical benefit in two double‐blind trials, novel c‐Abl inhibitors have been developed that accumulate in the brain and may inhibit c‐Abl at saturating levels. These novel inhibitors have demonstrated benefits in animal models of PD and have now entered clinical development. Here, we review the role of c‐Abl in the neurodegenerative disease process and consider the translational potential of c‐Abl inhibitors from model studies to disease‐modifying therapies for Parkinson's disease. © 2021 Inhibikase Therapeutics, Inc. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society. Abstract : The emergence of misfolded α‐synuclein in the substantia nigra as a result of oxidative/nitrosative stress, protein mutation, impaired clearance, and/or genetic factors leads to internalization of misfolded α‐synuclein, which activates the non‐receptor Abelson tyrosine kinase (c‐Abl), a key event in the initiation and progression of neurodegeneration in Parkinson's disease. c‐Abl activation both inactivates the ubiquitin E3 ligase parkin and creates the pathological form of α‐synuclein on the inside of the affected neurons, both events following specific tyrosine phosphorylation by c‐Abl. Treatment with a c‐Abl inhibitor reverses these processes, reactivating parkin and driving clearance of misfolded and pathological α‐synuclein through lysosomal and/or proteasomal processes. In model systems, these events result in substantial functional recovery in the brain and gastrointestinal (GI) tract. Although initial clinical trials of c‐Abl inhibitors failed, novel c‐Abl inhibitors thought to accumulate in the brain at concentrations sufficient to block c‐Abl are now being tested in the clinic and offer the opportunity to evaluate the potential of c‐Abl inhibition as a disease‐modifying therapy for patients with PD. January Infographic : Parkinson's Disease Modification through Abl Kinase Inhibition: An Opportunity